Saxifraga hirculus Linnaeus 1753 - Jarvis, Charlie (Linnaean Society of London in association with the Natural History Museum, 2007)
Saxifraga autumnalis Linnaeus, Species Plantarum 1: 402. 1753. "Habitat in humentibus Borussiae, Angliae, Helvetiae." RCN: 3160. Lectotype (Webb in Bot. J. Linn. Soc. 95: 264. 1987): [icon] " Saxifraga angustifolia autumnalis, flore luteo guttato " in Breyn, Exot. Pl. Cent.: 104, t. 48 [right half]. 1678. Current name: Saxifraga hirculus L. (Saxifragaceae). Published as part of Jarvis, Charlie, 2007, Chapter 7: Linnaean Plant Names and their Types (part S), pp. 806-877 in Order out of Chaos. Linnaean Plant Types and their Types, London :Linnaean Society of London in association with the Natural History Museum on page 820, DOI: 10.5281/zenodo.291971